Editorial - Nzaka Munga , Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2021)
Editorial NoteFive months after the first issue of MJTUM Volume 1 was published in December 2020, we are happy Volume 1 Issue 2 has also been finally published. This Issue comprises of a total of 7 original articles featuring review and research articles. The coverage of Volume 1 Issue 2 is relatively wide covering engineering, business, and public health domains. In the engineering domain, 2 papers bring out aspects of green energy and sustainable environment, an important aspect during this era of unprecedented climate change manifested by global sea surface temperature rise, sea level rise, ocean acidification, and increased incidences of cyclones. This has partly has been attributed to the production of greenhouse gases by man. The 2 papers therefore, point out possible innovative ways of reducing the emission of such greenhouse gases for a clean and sustainable environment.  In the business domain, the 2 papers have brought about improved business and production on researched impacts of firms’ performance by use of self-service technologies, as well as the engagement of firms’ employees on small and medium size enterprises. All this is dedicated to increasing firm efficiency and production. In the public health domain, MJTUM has featured 3 articles in which one has investigated on the current status of married pregnant women together with their couples taking HIV AIDS testing and counseling, an important exercise to reduce possible chances of HIV AIDS infection to new born babies from infected mothers. The ever increasing popularity of public transportation by commercial motor cycle riders has been investigated as a public health aspect on the rate of associated accidents mainly due to lack of observed cycling rules and training among riders. Finally, shisha consumption among students of higher learning institutions has also captured an emerging subject of public health worth further investigation. It is my hope that you will enjoy reading these articles.